S100B protein and neuron-specific enolase as predictors of postoperative cognitive dysfunction in aged dogs: a case-control study. (November 2020) - Zbóril, Sabrina; Schmidt, André P.; Oses, Jean P.; Wiener, Carolina D.; Portela, Luis V.; Souza, Diogo O.; Auler, José O.C.; Carmona, Maria J.C.; Fugita, Mariana S.; Flor, Patricia B.; Cortopassi, Silvia R.G.
Abstract: Objective: Postoperative cognitive dysfunction (POCD) may be related to brain injury. S100B protein and neuron-specific enolase (NSE) have been investigated as potential biochemical markers of neural cell injury in animals and humans. This study aimed to investigate the association between POCD, brain injury and serum concentrations of S100B and NSE after periodontal surgery in aged dogs. Study design: Prospective observational animal study. Animals: A total of 24 male and female dogs undergoing periodontal surgery. Methods: Dogs were separated into two groups based on age: control group, 10 dogs ≤ 8 years and aged group, 14 dogs > 8 years. Cognitive function was measured preoperatively and on the seventh postoperative day using the Canine Cognitive Dysfunction Rating scale and the Age-Related Cognitive and Affective Disorders scale. S100B protein and NSE serum concentrations were measured before and immediately after the surgery. Results: POCD was not observed after surgery in the present study. Serum concentrations of S100B and NSE were increased postoperatively in the control group but not in the aged group ( p  = 0.04 and 0.03, respectively). Preoperative S100B serum concentrations were significantly higher in the aged group ( p  = 0.01). Conclusions: There was no association between POCD and high concentrations of S100B and NSE in dogs. However, increased postoperative serum concentrations of S100B and NSE were found in the control group after surgery, an effect that may indicate neural damage. Clinical relevance: The results suggest that anesthesia and oral surgery are associated with higher postoperative serum concentrations of S100B and NSE in dogs ≤ 8 years old, which may indicate neural damage. Serum concentrations of S100B were elevated in aged dogs before anesthesia, a finding that might be related to chronic preoperative brain damage.